Soil amendments and pepper variety effects on soil physicochemical properties and yield of pepper in Ishiagu, Southeastern Nigeria - John Chukwu Nwite (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purpose: Poultry dropping and rice-mill wastes are generated in large quantities on daily basis in Ishiagu, Ebonyi State, Nigeria. These bio-wastes can improve soil quality and pepper production. Hence, this study seeks to evaluate the effects of amendments on soil physico-chemical properties and yield of pepper varieties.